2023
DOI: 10.1021/acsomega.2c06834
|View full text |Cite
|
Sign up to set email alerts
|

Growth of High-Purity and High-Quality Turbostratic Graphene with Different Interlayer Spacings

Abstract: Turbostratic graphene is a multilayer graphene, which has exotic electrical properties similar to those of monolayer graphene due to the low interlayer interaction. Additionally, the stacking structure of the turbostratic multilayer graphene can decrease the effect of attachment of charge impurities and surface roughness. This paper explores the growth of high-purity and high-quality turbostratic graphene with different interlayer spacings by calcining ferric chloride and sucrose at 1000 °C for 1 h under an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This is inconsistent with AB-stacked graphene, which is the lowest-energy configuration of multilayer graphene. , Because our graphene is transferred without intentional alignment, it is thus expected that the graphene samples are randomly rotated relative to each other, which is the signature of turbostratic graphene. Turbostratic graphene can be identified by the presence of low-intensity modes in the 1700–2300 cm –1 region of the Raman spectra. Figure c confirms the presence of the two signature modes of turbostratic graphene, labeled TS 1 and TS 2 . In addition, there is a low intensity peak around 1750 cm –1 , typically labeled the M band , that is not expected to be present in purely turbostratic graphene, but has previously been found to occur in some turbostratic few-layer graphene samples with relatively low I 2D / I G ratio. , Therefore, we conclude that we have produced low-defect density bi- and trilayer turbostratic graphene.…”
Section: Resultssupporting
confidence: 54%
“…This is inconsistent with AB-stacked graphene, which is the lowest-energy configuration of multilayer graphene. , Because our graphene is transferred without intentional alignment, it is thus expected that the graphene samples are randomly rotated relative to each other, which is the signature of turbostratic graphene. Turbostratic graphene can be identified by the presence of low-intensity modes in the 1700–2300 cm –1 region of the Raman spectra. Figure c confirms the presence of the two signature modes of turbostratic graphene, labeled TS 1 and TS 2 . In addition, there is a low intensity peak around 1750 cm –1 , typically labeled the M band , that is not expected to be present in purely turbostratic graphene, but has previously been found to occur in some turbostratic few-layer graphene samples with relatively low I 2D / I G ratio. , Therefore, we conclude that we have produced low-defect density bi- and trilayer turbostratic graphene.…”
Section: Resultssupporting
confidence: 54%
“…37 In 2023, our previous study showed that the main factor of the growth of turbostratic graphene was the fast cooling rate only. 41 However, the results in this report conrmed that the high pressure is also a key factor for the formation of turbostratic graphene.…”
Section: Resultsmentioning
confidence: 64%
“…This model also helps rationalize the larger experimental interlayer spacing when compared to the DFT-predicted value of 3.85 Å . For instance, turbostratic graphite is known to have an increased interlayer spacing, when compared to ordered graphite, by as much as 0.2 Å . Additional local defects, such as hydroxyl defects, may also locally deform layers and further increase the interlayer spacing.…”
Section: Resultsmentioning
confidence: 77%
“…21 For instance, turbostratic graphite is known to have an increased interlayer spacing, when compared to ordered graphite, by as much as 0.2 Å. 72 Additional local defects, such as hydroxyl defects, may also locally deform layers and further increase the interlayer spacing. The calculated powder diffraction pattern for a similar hypothetical structure with randomly stacked B 3 O 3 -based planar sheets exhibits similar suppression of many diffraction peaks; however, the remaining reflections do not match the experimental diffraction pattern as well as the planar B 4 O 2 -based layered structure.…”
Section: Layer Terminationmentioning
confidence: 99%